تصميم نظام تقني لرفع إنتاجية مطحنة المواد الخام في صناعة الاسمنت - الاحمد, نوفل; حسن, فواز (Latakia University Journal -Engineering Sciences Series, 2014)
تعتبر الطاقة بأنواعها كافة من أهم المعايير التي تؤخذ بالحسبان في أثناء تصميم أية منشأة وفي دراستنا هذه تم التركيز على منشأة الطحن(طحن المواد الأولية في معمل الاسمنت) والتي تستهلك كمية عالية من الكهرباء ويعتبر هذا الاستهلاك الكبير مؤشراً لتقييم الجدوى الاقتصادية حيث إنها تشكل حوالي 25% من تكلفة وحدة المنتج/1/. وقد عمدنا في هذه الدراسة على إجراء تعديلات لبعض نقاط الاختناق التي من شأنها تقليل الاستهلاك الكبير للطاقة في هذه المنشأة. Energy of all kinds is considered one of the most important criteria that can be taken into consideration when designing facilities. In this study, there is a great concentration on a milling plant (milling of materials in cement factory) that consumes a high quantity of electricity. This huge consumption is considered an indication for evaluating the economic efficiency. It forms about 25% of product cost. We also make modifications to some bottleneck points in the hope of reducing the high consumption of energy at this plant.